Application of the differential in approximate calculations: Application of the differential in approximate calculations - Tillabayev, B.SH. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation: in this article, explores the application of the differential in approximate calculations and explains it with examples. The obtained results are scientifically based